Quantitative mixed-valence state identification of metal ions based on fluorescence response of graphene quantum dots - Jing Xu; Juan Yang; Zhongteng Wang; Pei Li; Jian Lan; Risheng Yu; Jie Li; Lu Li; Wei Liu; Junlang Chen; Shangshen Feng; Liang Chen (Materials & Design, 2023)
Quantitative identification of mixed-valence metal ions is essential for gaining deeper insights into critical chemical and biological processes in environmental science, chemical engineering, and biological systems. However, a simple approach of quantitative identification mixed-valence metal ions in solution has remained a challenge. In this study, we have experimentally observed a significant linear correlation (R2 = 0.99) between the concentration of high-valence metal ions (using iron ions as an example) and the fluorescence intensity of graphene quantum dots (GQDs). Utilizing the distinct fluorescence responses of GQDs to high-valence and low-valence metal ions, reliable quantitative detection of mixed-valence metal ions has been successfully achieved. Remarkably, we introduced real-time monitoring of mixed-valence metal ions, revealing a shift from a molar ratio of approximately 4.0 to 2.0. Density functional theory calculations have revealed significant differences in charge transfer between high-valence and low-valence states of metal ions adsorbed onto GQDs. Furthermore, the versatility of this method can extend to various types of GQDs and metal ions, highlighting its universal applicability. This work presents a simple, convenient, and cost-effective approach for quantitatively identifying mixed-valence metal ions in solution, offering a new avenue and opportunity for applications in biochemistry, environmental science, catalysis and materials science.